The NEA 1993 Almanac of Higher Education - National Education Association, Washington, DC.; Robbins, Rebecca L.; National Education Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1993)
This 1993 Almanac of the National Education Association for the higher education sector offers, for the first time, faculty salary data, as well as a review of the year, a listing of resources, and analysis of policy developments. The faculty salary report analyzes the current state of academic salaries by rank and type of institution, and places this compensation data in historical perspective. The "Review of the Year" section begins with charts that compare bargaining and nonbargaining faculty salaries, state appropriations for higher education, and federal spending for higher education. This section also looks at 1992 campus trends throughout the country, higher education legislation, supreme court decisions, and a selected bibliography of higher education books. The"Resources and References" section lists schedules of upcoming academic meetings, prices and ordering information for higher education journals and reference aids, and current fellowship sources for faculty in higher education. The final section reprints the National Education Association's policy statements, resolutions, and legislative programs for the 103rd Congress. Also included is information on standing committees, advocacy groups for higher education, and a listing of higher education bargaining units that includes a listing of faculty and other professional and support personnel. (JB)
Availability: National Education Association, 1201 16th Street, N.W., Washington, DC 20036 (free to NEA members, $30 for nonmembers).
Teachers.
Administrators.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Collective Bargaining; College Faculty; Conferences; Court Litigation; Educational Finance; Faculty Fellowships; Faculty Organizations; Federal Aid; Federal Legislation; Higher Education; Professional Development; State Aid; Teacher Salaries; Unions; Almanac -- National Education Association; Reference Materials, General; Guides, Non-Classroom.